2021
DOI: 10.1038/s41598-021-91849-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and nonlinear influences of built environment factors on COVID-19 spread across townships in China at its initial stage

Abstract: The built environment can contribute to the spread of the novel coronavirus disease (COVID-19) by facilitating human mobility and social contacts between infected and uninfected individuals. However, mobility data capturing detailed interpersonal transmission at a large scale are not available. In this study, we aimed to objectively assess the influence of key built environment factors, which create spaces for activities—“inferred activity” rather than “actually observed activity”—on the spread of COVID-19 acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The impact of land use on the spread of COVID-19 is also measured by density and POIs. Higher density of specific land uses such as supermarkets, commercial land uses, clinics, hospitals, administrative, schools, shopping centers, and restaurants are found as the positive and significant predictors of COVID-19 cases in Tehran, Hong Kong, New York, Chicago, Wuhan and Huangzhou ( Ma et al, 2021 ; Nasiri et al, 2021 ; Li et al, 2020 ; Lak et al, 2021 ; Huang et al, 2021 , Huang et al, 2020 ; Yip et al, 2021 ). The high density of these land uses will contribute to higher POI and accordingly a higher rate of COVID-19 cases ( Xu et al, 2022 ; B. Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The impact of land use on the spread of COVID-19 is also measured by density and POIs. Higher density of specific land uses such as supermarkets, commercial land uses, clinics, hospitals, administrative, schools, shopping centers, and restaurants are found as the positive and significant predictors of COVID-19 cases in Tehran, Hong Kong, New York, Chicago, Wuhan and Huangzhou ( Ma et al, 2021 ; Nasiri et al, 2021 ; Li et al, 2020 ; Lak et al, 2021 ; Huang et al, 2021 , Huang et al, 2020 ; Yip et al, 2021 ). The high density of these land uses will contribute to higher POI and accordingly a higher rate of COVID-19 cases ( Xu et al, 2022 ; B. Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 96%
“…These are focused on the county (7), city (2), and urban district (22) scales (as shown in Table 3 ). The result of our review showed that land-use variables include 1. share of different land uses such as roads, open and green spaces ( Hassan et al, 2021 ; Kwok et al, 2021 ), 2. density of different land uses such as restaurants and clinics ( Ma et al, 2021 ; Huang et al, 2020 , Huang et al, 2021 ), 3. accessibility to different land uses such as commercial and educational ( Verma et al, 2021 ; Sun et al, 2021 ), 4. the mixture of land uses ( Li et al, 2020 ; Wali and Frank, 2021 ) and 5. Point of Interest (POI) for different land uses ( Xu et al, 2022 ; B. Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first six features with the highest feature importance are selected to draw partial dependence plots ( Ma et al, 2021 ) for further analysis. The partial dependence plots of X 4 , X 6 , X 5 , X 1 , X 18 , and X 16 and each of the clusters are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the pre-COVID-19 the literature demonstrated different transport modes ( Findlater and Bogoch, 2018 ) as a direct factor affecting infectious diseases transmission ( Zhang et al, 2020a , Zhang et al, 2020b , Peak et al, 2018 , Arthur et al, 2017 , López-Quílez, 2019 ). The recent COVID-19 literature focused on built environment factors ( Ma et al, 2021 ), urban attributes ( Barak et al, 2021 ), and living conditions ( Sahasranaman and Jensen, 2021 ) to investigate the income on cases growth. The built environment plays a pivotal role in people health and well-being ( Angiello, 2021 ): density of schools, commercial and sport centers, proportion of built-up areas, building systems and nighttime light, socioeconomic and demographic characteristics have been identified have as key drivers of the SARS-CoV-2 transmission and infection ( Verma et al, 2021 , Barak et al, 2021 , Corazza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%